Pembelajaran Anak Usia Dini Berbasis Kearifan Budaya Lokal Lagu Pantai Panjang di TK Baitul Izzah Kota Bengkulu - Amalia, Ria; Nur Umairoh, Sheny; Tri Amelia, Viola; Syafri, Fatrica (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to explore the effectiveness of local cultural wisdom-based learning through the song “Pantai Panjang” in early childhood. The research method used is qualitative. Data were collected through observation, interviews, and analysis of relevant literature. The results show that the song “Pantai Panjang” is effective in instilling values such as cooperation, honesty, and togetherness in children. It also increases children's engagement and interest in learning activities. In addition, the song helps children understand and appreciate their local culture, which is important for the development of their cultural identity. Regularly singing this song in educational and family settings also strengthens children's social and emotional connections to their culture. This study concludes that using the song “Pantai Panjang” as a learning medium based on local cultural wisdom is an effective strategy to support early childhood character and cultural development. The integration of this song in the early childhood education curriculum can make a significant contribution to character building, moral values and cultural understanding in young children.